Interexaminer agreement among pediatric dental specialists in assessment of tonsil size, Friedman tongue position, and Friedman staging of obstructive sleep apnea in children: An observational study - Lekshmy S. R. Nair; Sageena George; S. Anandaraj; S. Anuja; T. V. Naveena; U. Aishwarya (Wolters Kluwer Medknow Publications, 2024)
Background: The evaluation of tonsil size, Friedman Tongue Position (FTP), and Friedman staging in pediatric obstructive sleep apnea (OSA) holds significant clinical importance, offering manifold advantages in diagnosis and surgical management. Aims and Objectives: This study aimed to assess the reliability of pediatric OSA evaluation by determining inter-examiner agreement among pediatric dental specialists. Materials and Methods: Conducted at the Department of Pediatric Dentistry, PMS College of Dental Science and Research Hospital (2023-2024), this observational study utilized conventional consulting rooms, headlights, and examination chairs. Thirteen medical practitioners reviewed video recordings of the oropharyngeal regions of twelve pediatric patients exhibiting mouth breathing. Friedman staging was determined based on tonsil size and tongue position gradings.Inter-examiner agreement was evaluated using Fleiss kappa analysis. Results: Observers, including residents and practitioners in pediatric dentistry, demonstrated poor agreement regarding FTP and tonsil grading. Conclusion: Understanding the nuances of tonsil size and FTP in pediatric OSA evaluation, along with identifying avenues for refinement, can enhance medical decision-making among healthcare providers, including pediatric dentists.